Sustainable development, noosphere and spatial organization of society in the subject field of sociaty geography - Sergiy Sonko (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2016)
The article is devoted to the noospherical evolution of the spatial organization of society. One of the main noospherical provisions of HomoSapiens ecology is the fact that this species is an equal participant in the natural material-energy cycle but it has expanded limits of its ecological niche by advancing in time natural processes (“traps for time”) and the spatial transformation of its ecotope (“traps for space”). In addition, this space-time transformation significantly increased the level of planetary entropy (“trap for information”).